Accelerated degradation of polymer electrolyte membrane fuel cell gas diffusion layers I. Methodology and surface characterization - Liu, Hang; George, Michael G.; Messerschmidt, Matthias; Zeis, Roswitha; Kramer, Dominik; Scholta, Joachim; Bazylak, Aimy (Journal of The Electrochemical Society, 2017)
In this work, an ex situ accelerated carbon-corrosion-based ageing methodology is presented for stand-alone gas diffusion layers (GDLs). Pristine GDLs were subjected to carbon corrosion (degradation) via submersion in a hydrogen peroxide (H2O2) solution. The microporous layer (MPL) experiences up to nine times the loss in carbon mass compared to the carbon fiber substrate. The hydrophobicity of the GDL is also degraded as evidenced by a reduction in the surface contact angle, and this loss of hydrophobicity is associated with surface corrosion and polytetrafluoroethylene (PTFE) degradation. Performance testing reveals increases in mass transport losses for aged GDLs, which is a phenomenon that is attributed to the reduction in GDL hydrophobicity.
CRIS-Team Scopus Importer:2023-08-01